2022
DOI: 10.3389/fimmu.2022.960411
|View full text |Cite
|
Sign up to set email alerts
|

Decoding human-macaque interspecies differences in Fc-effector functions: The structural basis for CD16-dependent effector function in Rhesus macaques

Abstract: Fc mediated effector functions of antibodies play important roles in immunotherapies and vaccine efficacy but assessing those functions in animal models can be challenging due to species differences. Rhesus macaques, Macaca mulatta (Mm) share approximately 93% sequence identity with humans but display important differences in their adaptive immune system that complicates their use in validating therapeutics and vaccines that rely on Fc effector functions. In contrast to humans, macaques only have one low affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Prior work by Chan and collaborators also found that the I158 allotype (FcγR3A-1) had slightly higher binding capabilities than the V158 allotype (FcγR3A-3) when measured using BLI although the differences were not significant ( 27 ). The greater IgG binding capabilities of I158 compared to V158 was confirmed by Tolbert et al., except for rhesus FcγRIII V158 binding more tightly to rhesus IgG4 than I158 ( 38 ). Further, both Chan et al.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Prior work by Chan and collaborators also found that the I158 allotype (FcγR3A-1) had slightly higher binding capabilities than the V158 allotype (FcγR3A-3) when measured using BLI although the differences were not significant ( 27 ). The greater IgG binding capabilities of I158 compared to V158 was confirmed by Tolbert et al., except for rhesus FcγRIII V158 binding more tightly to rhesus IgG4 than I158 ( 38 ). Further, both Chan et al.…”
Section: Discussionmentioning
confidence: 76%
“…We also identified three synonymous SNPs. AlphaFold2 predictions indicate that SNPs V215I and V211M occur in the cytoplasmic tail, and I158V and A8S occur in the extracellular domain ( Figure 5B ) ( 29 , 38 ). The I158V SNP occurs at the same Fc-FcR contact region ( Figure S2D ) as the human FcγRIIIa V158F.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody-dependent cellular cytotoxicity was measured by NK cell degranulation using NK92.rh.158I.Bb11, an engineered NK cell line expressing the Ile 158 variant of rhesus macaque CD16 (33). Confluent TeloRF cells were infected with 1 MOI UCD52 RhCMV in low serum (5%) medium in T75 flasks (ThermoFisher).…”
Section: Serology Assaysmentioning
confidence: 99%
“…In contrast, FcγRIIIB has no transmembrane region and intracellular region, but is anchored to the cell membrane by glycosylphosphatidylinositol (GPI), which is effective for human IgG1 and IgG3 binding [ 7 , 8 ]. To date, several structures of the extracellular domain of huFcγRIII in complex with IgG1-Fc showed that the EC2 domain of the low-affinity FcγRIII is docked into the horseshoe opening of a homodimeric Fc region on IgG1, providing a novel strategy to design small peptides for regulating the interaction of IgG1 to FcγRIII [ 9 , 10 , 11 , 12 , 13 , 14 ]. It has actually been reported that the peptides of human IgG are able to bind with FcγR molecules [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%